DOES THE INTERNATIONAL TOURISM INDUSTRY RELAX SOVEREIGN CREDIT RATINGS: THE CASE OF SELECTED MEDITERRANEAN COUNTRIES (The South East European Journal of Economics and Business, 2018)
Sustainable tourism plays a dominant role in the economic well-being of the Mediterranean countries, especially small ones. Tourism earnings account for a significant proportion of their GDP, and they have an overwhelming reliance on tourism as a source of exports. The general trends in tourism earnings and volatilities in country risk ratings often go hand in hand, especially for small touristic countries in that region. The research presented in this paper provides a comparative assessment of the international country risk ratings and highlights the importance of the tourism earnings and export. This study employs the ordered response and Poisson count panel data model for a sample of ten Mediterranean countries. The aim of this study is to investigate whether the tourism determinants of sovereign credit ratings for Mediterranean countries vary between different rating agencies (Standard & Poor’s, Moody’s and Fitch’s). The key finding is that an increase in tourism earnings as a proportion of GDP and as the main export share in the total country export impairs the sovereign risk rating and turns out to be robust across the different methodologies.Keywords: tourism earnings, sovereign credit ratings, Mediterranean countries, ordered response panel model